BUILDING ENVELOPE COMPONENT TO CONTROL THERMAL INDOOR ENVIRONMENT IN SUSTAINABLE BUILDING: A REVIEW - Abraham Seno Bachrun; Ting Zhen Ming; Anastasia Cinthya (SINERGI, 2019)
The engineering of building envelope aims is to achieve building energy efficiency which uses shading device to increase the shaded area. Also, to reduce heat gain by the building from solar radiation, this will reduce the energy load on the building. This paper aim to focuses on the deepening of technology of building envelope elements, and how the building envelope can control the thermal comfort as part of the indoor environment in a building that carries sustainability architecture. In conclusion, finally, reveal that the principles of passive design on building envelope have a great influence on the comfort level in the building. It is not possible to create a design that meets the thermal comfort requirements by emphasizing the design of building envelopes. The goal to be achieved in sustainable design is to minimize the use of the current design that takes much energy (almost14% world energy consumption) to address the issue of energy crisis lately.